GTP-Binding-Defective ARL4D Alters Mitochondrial Morphology and Membrane Potential - Li, Chun-Chun; Wu, Tsung-Sheng; Huang, Chun-Fang; Jang, Li-Ting; Liu, Yu-Tsan; You, Shu-Ting; Liou, Gunn-Guang; Lee, Fang-Jen S. (PloS one, 2012)
ARL4D, ARL4A, and ARL4C are closely related members of the ADP-ribosylation factor/ARF-like protein (ARF/ARL) family of GTPases. All three ARL4 proteins contain nuclear localization signals (NLSs) at their C-termini and are primarily found at the plasma membrane, but they are also present in the nucleus and cytoplasm. ARF function and localization depends on their controlled binding and hydrolysis of GTP. Here we show that GTP-binding-defective ARL4D is targeted to the mitochondria, where it affects mitochondrial morphology and function. We found that a portion of endogenous ARL4D and the GTP-binding-defective ARL4D mutant ARL4D(T35N) reside in the mitochondria. The N-terminal myristoylation of ARL4D(T35N) was required for its localization to mitochondria. The localization of ARL4D(T35N) to the mitochondria reduced the mitochondrial membrane potential (ΔΨm) and caused mitochondrial fragmentation. Furthermore, the C-terminal NLS region of ARL4D(T35N) was required for its effect on the mitochondria. This study is the first to demonstrate that the dysfunctional GTP-binding-defective ARL4D is targeted to mitochondria, where it subsequently alters mitochondrial morphology and membrane potential.